Oral mucosal lesions in Indigenous people of Sarawak and their related habits - Rahman, Z.A.A.; Zain, R.B.; Abang, Z.; Ikeda, N.; Razak, I.A.; Fukano, H.; Abdullah, F.; Hii, M. (1999)
The Malaysian nationwide survey on oral mucosal lesions (OML) in 1993/94 showed a low prevalence of OML in particular oral cancer and precancer (OPC) among the Malays as compared to the Indians and the Indigenous people of Sabah and Sarawak. A low prevalence of quid chewing habit was also noted in the Malays in that survey. The present study was conducted to investigate whether the low prevalence of OPC in the Malays was attributed to the low prevalence of quid users among the Malays and/or whether the quid contents used were different. Two examiners were trained prior to the survey. The interexaminer consistency of diagnosing the presence or absence of lesions was 91.3. An interview on their oral habits was also done. The mean age of 276 subjects examined was 61.1Â±10.0 years. There were 23.6 men and 76.4 women. Among the subjects interviewed, 41.7 were smokers and 37.7 were quid chewers. The prevalence of OML was 20.3 while OPC was found in only 1.4 of the subjects examined. Among the quid chewers and non-quid chewers, the prevalence of OML was found to be 35.6 and 11 respectively. However ,the prevalence of OPC ( only leukoplakia and lichen planus were detected; cancer, erythroplakia and oral submucous fibrosis were absent) was equally low in both groups (1.9 among quid chewers and 1,2 among non-quid chewers). Such low prevalence of OPC among Malay quid chewers, differed from reported higher prevalences of OPC in the Malaysian Indians and the indigenous people of Sarawak. A further analysis of the quid contents showed a low usage of tobacco (3.8) in the quid mixtures chewed by these subjects as compared to the quid mixtures reportedly used by the Indians and the indigenous people of Sarawak. It is concluded that the lack of tobacco in the quid mixtures used by the Malays may be related to the low prevalence of OPC in Malay quid chewers.